The Effect of Corporate Life Cycle on Corporate Restructuring - Nur Afiqoh Sari (Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine the effect of corporate life cycle on restructuring decisions with governance and financial distress as moderating variables in manufacturing companies listed on the Indonesia Stock Exchange in five years (2013-2017) and there are 480 data for the sample. The hypotheses tested using logistic regression. The results of this study indicate that life cycle has an effect on restructuring decisions. Financial distress strengthen the influence of the